Variación de las cuentas por cobrar en la Cooperativa de Ahorro y Crédito Juan Pío de Mora Ltda. sucursal Babahoyo en el período 2022 – 2023. - Cabello Herrera, Shirley Jamileth (2024)
The correct control of Accounts Receivable in a financial institution determines its liquidity and profitability, however, not having good control of them can cause losses at the end of an accounting period, for this reason the This case study proposes to analyze the variation that existed in the Accounts Receivable of the branch of the “Juan Pío de Mora” Savings and Credit Cooperative Ltda. located in the city of Babahoyo in order to determine the main causes of its variations, know the percentage of delinquency and liquidity of the company using different methodologies and research methods and demonstrate how these variables affect the financial performance of the entity throughout these accounting periods (2022,2023).